Effect of Evidence and Changes in Reimbursement on the Rate of Arthroscopy for Osteoarthritis. (May 2013) - Holmes, Robert; Moschetti, Wayne; Martin, Brook; Tomek, Ivan; Finlayson, Samuel
Background: The efficacy of arthroscopic debridement or lavage for knee osteoarthritis (OA) was cast into doubt after publication of several randomized controlled trials beginning in 2002. Purpose: The authors set out to determine whether evidence of ineffectiveness, along with subsequent changes in reimbursement, were followed by changes in utilization rates of arthroscopy for patients with OA. Study Design: Cohort study (prevalence); Level of evidence, 2. Methods: The Florida State Ambulatory Surgery Database was used to examine population-based rates of knee arthroscopy from 2000 to 2008 for patients with and without the diagnosis of OA; data were stratified between public and private payers. These trends were compared with patients who underwent arthroscopy for other diagnoses and were also compared with patients whose arthritis was not the primary indication for surgery. Results: A 39% decrease in the adjusted population-based rate of knee arthroscopy for OA was observed, from 12.2 per 100, 000 adults in 2000 (95% CI, 9.9-14.4) to 7.7 per 100, 000 adults in 2008 (95% CI, 6.7-8.6). The overall rate among individuals with a primary diagnosis of OA significantly decreased for both public ( P < .001) and private insurance ( P = .001) and the rate of this decrease was similar between the two insurance types ( P = .610). Although the unadjusted rates for all knee arthroscopy increased over the study period, the rate of increase was slowed in the years following the publication of several randomized controlled trials and subsequent changes in reimbursement. The average effect on arthroscopy rates attributed to these events was a reduction in 12 per 100, 000 private arthroscopies (95% CI, –16.3 to 40.6; P = .404) and 35.7 per 100, 000 publicly insured arthroscopies (95% CI, 15.0-56.4; P = .001). Conclusion: Evidence of the lack of efficacy of arthroscopy for knee OA, along with changes in reimbursement, preceded a significant decline in the population-based rates of this procedure in both publicly and privately insured patients in Florida.